Chinatown film culture : the appearance of cinema in San Francisco's Chinese neighborhood - Fahlstedt, Kim K (New Brunswick : Rutgers University Press, 2020)
"Chinatown Film Culture provides the first comprehensive account of the emergence of film and moviegoing in the transpacific hub of San Francisco in the early twentieth century. Working with materials previously left in the margins of grand narratives of history, Kim K. Fahlstedt uncovers the complexity of a local entertainment culture that offered spaces where marginalized Chinese Americans experienced and participated in local iterations of modernity. At the same time, this space also fostered a powerful Orientalist aesthetic that would eventually be exported to Hollywood by San Francisco showmen such as Sid Grauman. Instead of primarily focusing on the screen-spectator relationship, Fahlstedt suggests that immigrant audiences' role in the proliferation of cinema as public entertainment in the United States saturated the whole moviegoing experience, from outside on the street to inside the movie theater. By highlighting San Francisco and Chinatown as featured participants rather than bit players, Chinatown Film Culture provides an historical account from the margins, alternative to the more dominant narratives of U.S. film history"--
Early Film in San Francisco. Bold Visions and Frontier Conditions: The Emergence of Film in San Francisco -- "If I Had the Power to Do So I Would Destroy Them with My Own Hands": Film and Politics in Post-Quake San Francisco -- Chinatown Exhibition and Movie Theaters -- "The Most Cosmopolitan City in the World": Chinese San Francisco at the Turn of the Twentieth Century -- "Eyes Darting Around, Spirit Dashing About" -- Mapping Chinatown Film Culture, 1906-1915 -- The Chinesque Aesthetic: Orientalist Stereotypes in Post-Quake Film Culture -- Chinese American Audiences. "Where the People Aren't All American": Chinatown Audiences and Spectators -- Chinatown Modernity: Revolutions and Movie Theaters -- Trajectories and Concluding Remarks.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Motion picture audiences -- California -- San Francisco -- History; Chinese -- California -- San Francisco -- Social life and customs; Chinese in motion pictures; Motion picture theaters -- California -- San Francisco -- History; Motion pictures -- Social aspects -- California -- San Francisco; Chinatown (San Francisco, Calif.) -- Social life and customs; Cinéma -- Publics -- Californie -- San Francisco -- Histoire; Chinois -- Californie -- San Francisco -- Mœurs et coutumes; Chinois au cinéma.; Cinéma -- Aspect social -- Californie -- San Francisco; PERFORMING ARTS -- General; Chinese in motion pictures; Chinese -- Social life and customs; Manners and customs; Motion picture audiences; Motion picture theaters; Motion pictures -- Social aspects; California -- San Francisco; California -- San Francisco -- Chinatown; History